Morphology and multi-gene phylogeny reveal a new Brunneofusispora species from coffee in Yunnan Province, China - Liu, Xiangfu; Tibpromma, Saowaluck; Karunarathna, Samantha C.; Chethana, K.w.t.; Lu, Li; Dai, Dongqin; Elgorban, Abdallah M.; Hyde, Kevin D. (Phytotaxa, 2024)
Coffee is one of the most important cash crops native to north-central Africa, and the second most popular beverage ingredient worldwide. Coffee-associated fungal pathogens have been well studied, but few studies have reported saprobes of coffee. In China, Yunnan Province is the main region of coffee plantations and production. To investigate saprobic fungi of coffee plants, dead branches of Coffea with fungal fruiting bodies were collected in Baoshan City, Yunnan Province, China. Multi-gene phylogenetic analyses of SSU, ITS, LSU, RPB2, and TEF1-α sequence data indicated that our collections formed an independent branch within Brunneofusispora and sister to B. sinensis. The new species B. baoshanensis, characterized by uniloculate ascomata with an erumpent long neck, and inequilateral, ends acute, 1-septate, constricted at the septum ascospores with mucilaginous sheath, was identified based on morphology and multi-gene phylogeny. This is the first report of Brunneofusispora species isolated from Coffea in China. A complete description, micrographs, and a phylogenetic tree showing the placement of the new species are provided.